Frekuensi Penggunaan Media Sosial di Era Digital: Peluang Bisnis bagi Mahasiswa Nusa Tenggara Timur dalam Konteks Keragaman Budaya - Kelin, Selus Paru; Taka, Linda Marlince; Koinmanas, Habel Ada; Djelo, Apriana Kale; Keren, Meilyuani Ivana Mirandha (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study aims to explore the level of social media usage among East Nusa Tenggara (NTT) students and analyze the potential of social media in creating local culture-based business opportunities. Using a descriptive quantitative approach, it involved 100 students from various educational and cultural backgrounds. The results of this study revealed that NTT students actively utilize various social media platforms, especially Facebook, Instagram, and TikTok. It shows that social media is not only a means of communication, but also a promising business opportunity. NTT's rich cultural diversity, such as traditions, arts, and culinary, can be effectively promoted through attractive visual content on these platforms. Students can utilize social media to create a personal brand, collaborate with local influencers, and reach a wider market, both domestic and international. This study identified that despite the great potential, many students have not fully utilized social media as a tool for doing business. Therefore, this study suggests several strategies to maximize the potential of social media in developing culture-based businesses, including: building content based on local cultural stories through the stories feature, utilizing short videos to attract attention on TikTok, providing educational content on YouTube, and combining cross-platform use. Thus, with the right utilization of social media, students can contribute to the local economy and preserve NTT culture.